Knee extension strength and handgrip strength are important predictors of Timed Up and Go test performance among community-dwelling elderly women: a cross-sectional study - Felício, Diogo Carvalho; Elias Filho, José; Queiroz, Bárbara Zille de; Diz, Juliano Bergamaschine Mata; Pereira, Daniele Sirineu; Pereira, Leani Souza Máximo (São Paulo Medical Journal, 2021)
BACKGROUND: Handgrip and knee extension strengths have each been used to characterize disability. However, it has been reported that the association between handgrip and knee extension strengths is weak. OBJECTIVE: To evaluate the influence of knee extensor and handgrip muscle strength on Timed Up and Go (TUG) test results among elderly women with worse (≥ 10 seconds) and better (< 10 seconds) performance, after controlling for confounders. DATA AND SETTING: Cross-sectional study on a sample selected according to convenience, carried out in a federal public institution of higher education. METHODS: Assessment of handgrip was carried out using the Jamar dynamometer (Lafayette Instrument Company, Inc., Lafayette, United States). Knee extensor muscle performance was measured using an isoki- netic dynamometer (Biodex System 3 Pro; Biodex Medical Systems, Inc., United States), The confounding factors were education, age, comorbidities, body mass index and Geriatric Depression Scale and Human Activity Profile scores. Functional performance was assessed through the TUG test. A backward linear regression model was used. RESULTS: 127 elderly women performed the TUG test in more than 10 seconds and 93 in less than 10 seconds. However, regardless of test performance, handgrip strength and knee extension strength comprised the reduced final model. CONCLUSIONS: Knee extension strength and handgrip strength might be particularly useful indicators for measuring disability.